The Greening of Global Value Chains: Insights from the Furniture Industry. (1st October 2013) - De Marchi, Valentina; Maria, Eleonora Di; Ponte, Stefano
Abstract : With increasing fragmentation of production between independent firms that are spatially dispersed and are responsible for different steps of the production process, a Global Value Chain approach is employed to examine how 'lead firms' shape the green features of upstream activities. Comparative case studies in the Italian furniture industry (Ikea, Valcucine) are used to show that lead firms implement 'hands-on' governing mechanisms to improve the environmental performance of their value chain partners — moving away from the market but still avoiding vertical integration — but also 'hands-off' mechanisms embedded in standards and design. Two governing approaches to the greening of value chains are identified: standard-driven and mentoring-driven, and these are used to provide some reflections on when we are likely to observe one or the other, and also to develop a future research agenda.